Inter vivos transfers of ownership in family firms - Niklas Potrafke; James R. Hines; Marina Riem; Christoph Schinke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We examine the determinants of inter vivos transfers of ownership in German family firms between 2000 and 2013. Survey evidence indicates that owners of larger firms, and firms with strong current business conditions, transfer ownership at higher rates than others. When a firm's self-described business condition improves from “normal” to “good” the chance of an inter vivos transfer increases by 46 percent. Inter vivos transfer rates also rose following a 2009 transfer tax reduction. These patterns suggest that trans-fer taxes significantly influence rates and timing of inter vivos ownership transfers.
Keywords: H24; D31; D22; 330